Surface current balance and thermoelectric whistler wings at airless astrophysical bodies: Cassini at Rhea. Issue 11 (10th November 2014) - Teolis, B. D.; Sillanpää, I.; Waite, J. H.; Khurana, K. K.
Abstract Sharp magnetic perturbations found by the Cassini spacecraft at the edge of the Rhea flux tube are consistent with field‐aligned flux tube currents. The current system results from the difference of ion and electron gyroradii and the requirement to balance currents on the sharp Rhea surface. Differential‐type hybrid codes that solve for ion velocity and magnetic field have an intrinsic difficulty modeling the plasma absorber's sharp surface. We overcome this problem by instead using integral equations to solve for ion and electron currents and obtain agreement with the magnetic perturbations at Rhea's flux tube edge. An analysis of the plasma dispersion relations and Cassini data reveals that field‐guided whistler waves initiated by (1) the electron velocity anisotropy in the flux tube and (2) interaction with surface sheath electrostatic waves on topographic scales may facilitate propagation of the current system to large distances from Rhea. Current systems like those at Rhea should occur generally, for plasma absorbers of any size such as spacecraft or planetary bodies, in a wide range of space plasma environments. Motion through the plasma is not essential since the current system is thermodynamic in origin, excited by heat flow into the object. The requirements are a difference of ion and electron gyroradii and a sharp surface, i.e., without a significant thick atmosphere.